LA OBESIDAD Y SU RELACIÓN CON EL CÁNCER DE MAMA EN UNA POBLACIÓN MEXICANA OBESITY AND ITS RELATION TO BREAST CANCER IN A MEXICAN POPULATION - Vega-Malagón, Genaro; Ávila-Morales, Javier; García-Solís, Pablo; Camacho-Calderón, Nicolás; Becerril-Santos, Alma (European Scientific Journal, ESJ, 2014)
OBJECTIVE: To determine the relationship between obesity and breast cancer in a Mexican population. METHODOLOGY. - Case-control study in General Hospital of Queretaro, México; January 2003 to December 2008; cases: 60 women with histologically confirmed breast cancer, controls: 60 women with negative mammography cancer, anthropometric variables were analyzed odds ratio with confidence interval of 95%, Student’s t test and x-squared. RESULTS. - The average age was similar in both groups, in the cases was 52.65 years (SD 11.80) and controls 52.01 (SD 11.15), with p> 0.05, anthropometric factors were statistically significant (p ≤ 0.05) were weight, body mass index ≥ 25 (OR: 6.05, 95% CI 2.53-14-47) Abdominal circumference ≥ 88 cm. (OR: 2.58, 95% CI 1.11-5.96), waist-hip index ≥ 0.86 (OR: 3.50, 95% CI 1.55-7.87). CONCLUSIONS. - It is important to determine the anthropometric measurements of women and identify those at risk for breast cancer to conduct close monitoring and early detection of this disease.